Corpora, Serendipity & Advanced Search Techniques - Michael Wilkinson (JoSTrans: The Journal of Specialised Translation)
Exploring corpora with concordancers can help translators to improve the quality of their translations by, for example, providing them with information about collocates; by helping them to choose between terms; or by enabling them to confirm intuitive decisions. But corpora also allow unpredictable, incidental learning: the user may notice unfamiliar uses in a concordance and follow them up by exploratory browsing. The article discusses the potential of corpora to throw up previously unknown information that may be relevant to a translation assignment, and illustrates how advanced search strategies can increase the likelihood of “accidentally” finding relevant information.